Endoplasmic reticulum stress and intestinal inflammation - Kaser, A (Mucosal Immunol, 2009)
The intestinal epithelial cell (IEC) is increasingly recognized to play a prominent role as an important intermediary between the commensal microbiota and the intestinal immune system. Moreover, it is now recognized that intestinal inflammation in inflammatory bowel disease (IBD) may arise primarily from IEC dysfunction due to unresolved endoplasmic reticulum (ER) stress as a consequence of genetic disruption of X box binding protein-1 function. In addition to primary (genetic) abnormalities of the unfolded protein response, a variety of secondary (inflammation and environmental) factors are also likely to be important regulators of ER stress. ER stress pathways are also well known to regulate (and be regulated by) autophagy pathways. Therefore, the host’s ability to manage ER stress is likely to be a major pathway in the pathogenesis of intestinal inflammation that arises primarily from the IEC. Herein we discuss ER stress in the IEC as both an originator and perpetuator of intestinal inflammation in IBD.